2021
DOI: 10.1111/dth.15099
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoscopic assessment of treatment response in patients undergoing autologous non‐cultured epidermal cell suspension for the treatment of stable vitiligo: A prospective study

Abstract: There is lack of literature on serial dermatoscopic assessment in patients undergoing non‐cultured epidermal cell suspension (NCES) for treatment of stable vitiligo. This prospective study was conducted to evaluate the role of serial dermatoscopy in assessing disease stability and predicting repigmentation rates in vitiligo patients undergoing NCES. Dermatoscopic assessment of target lesions were done at baseline and post‐NCES at week 4, 8, 12, 16, and 24. Patches obtaining >90% repigmentation at 24 weeks were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…The early lesions often are hypopigmented (rather than complete that pigment network changes are seen in evolving vitiligo while these changes are seen less frequently in stabilized or repigmenting vitiligo (Dev et al, 2021;Jha et al, 2018;Kumar Jha et al, 2018;Nirmal et al, 2019;Thatte & Khopkar, 2014). The study conducted by Benzekri et al also found that the hypomelanotic with poorly defined borders lesions are associated with disease activity (Benzekri & Gauthier, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The early lesions often are hypopigmented (rather than complete that pigment network changes are seen in evolving vitiligo while these changes are seen less frequently in stabilized or repigmenting vitiligo (Dev et al, 2021;Jha et al, 2018;Kumar Jha et al, 2018;Nirmal et al, 2019;Thatte & Khopkar, 2014). The study conducted by Benzekri et al also found that the hypomelanotic with poorly defined borders lesions are associated with disease activity (Benzekri & Gauthier, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Regarding intralesional telangiectasia, previous studies have suggested it to be the marker of repigmenting disease (Jha et al, 2018; RuSong et al, 2009). However, the study by Dev et al (2021) suggested that appearance of telangiectasia significantly reduces the odds of excellent repigmentation after surgical management. As this study included lesions, which were already stable and evaluated after administration of surgical treatment, the findings of this study are difficult to generalize for active lesions on medical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, dermoscopy and RCM have been reported to be reliable techniques to evaluate initial treatment response as they can show increases in perilesional and intralesional pigmentation that are not visible to the naked eye. [34][35][36] In our study, the clinical, dermoscopic and RCM changes of 92 patients before and after treatment were compared and the following conclusions were found. Before the skin lesions recovered clinically, dermoscopy had observed increased pigmentation in the skin lesions.…”
Section: Discussionmentioning
confidence: 99%